2018
DOI: 10.1021/acs.jpcc.7b10208
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of the Structural Stabilities of Ceria Surfaces and Supported Metal Nanocluster in Vapor and Aqueous Phases

Abstract: In the present work, the stabilities of three low-index ceria (CeO 2 ) surfaces, that is, ( 111), (110), and (100) in vapor and aqueous phases were studied using ab initio molecular dynamics (AIMD) simulations and density functional theory calculations. On the basis of the calculated Gibbs surface free energies, the morphology and exposed surface structures of the CeO 2 nanoparticle were predicted using the Wulff construction principle. It is found that the partially hydroxylated ( 111) and (100) are two major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…However, it is known since 1970s that clusters majorly change shapes in the presence of the support—a concept of strong metal–support interaction (SMSI), and also the adsorbates . For instance, it has been shown that Pt 13 cluster shape will significantly change when deposited on CeO 2 . Even different surface cuts could lead to different stable cluster structures: Ab initio molecular dynamics (AIMD) simulations revealed that the CeO 2 (110) surface provides the most stability for the Pt 13 nanocluster (Figure ).…”
Section: The Global Minimum Structure Of the Cluster Catalyst: Not Trmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is known since 1970s that clusters majorly change shapes in the presence of the support—a concept of strong metal–support interaction (SMSI), and also the adsorbates . For instance, it has been shown that Pt 13 cluster shape will significantly change when deposited on CeO 2 . Even different surface cuts could lead to different stable cluster structures: Ab initio molecular dynamics (AIMD) simulations revealed that the CeO 2 (110) surface provides the most stability for the Pt 13 nanocluster (Figure ).…”
Section: The Global Minimum Structure Of the Cluster Catalyst: Not Trmentioning
confidence: 99%
“…Ce (light yellow), O (red), Pt (cyan), and H (white). Adapted with permission from Reference . Copyright 2018 American Chemical Society…”
Section: The Global Minimum Structure Of the Cluster Catalyst: Not Trmentioning
confidence: 99%
“…Several methods have been proposed to characterize the electron transfer around the interfacial area, e.g., work function (Liu et al, 2016 ), Bader charge analysis (Lim and Wilcox, 2011 ; Ewing et al, 2015 ), and charge density difference (Wang Y. et al, 2017 ; Ren et al, 2018 ). Basically, the work function can be defined as ϕ = E vac − E F , where E F is the Fermi energy and E vac denotes the electrostatic potential of the vacuum level.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods have been proposed to characterize the electron transfer around the interfacial area, e.g., work function (Liu et al, 2016), Bader charge analysis (Lim and Wilcox, 2011;Ewing et al, 2015), and charge density difference (Wang Y. et al, 2017;Ren et al, 2018). Basically, the work function can be defined as φ = E vac − E F , where E F is the Fermi energy and E vac denotes the FIGURE 3 | The calculated total density of states (TDOS) for (A) the icosahedron Pt 13 cluster, (B) the clean 20%-MIL-125-(SCH 3 ) 2 (001) surface, and (C) the optimized Pt 13 /20%-MIL-125-(SCH 3 ) 2 system (the Pt 13 cluster is spin-polarized).…”
Section: Electron Transfer Properties Across the Pt13/20%-mil-125-(scmentioning
confidence: 99%
“…For example, it is reported that the supported Pt 13 nanocluster has the tendency to wet the CeO 2 surface in the gas phase (CO) due to the strong MSI. Notably, this MSI is clearly enhanced with the presence of the aqueous phase …”
Section: The Thermal Stability Of Supported Metal Nanoparticlesmentioning
confidence: 99%